Spatial dynamics of labor markets in Brazil - Chomitz, Kenneth M.; World Bank (Policy research working paper, 2005)
"There was substantial spatial variation in labor market outcomes in Brazil over the 1990s. In 2000, about one-fifth of workers lived in apparently economically stagnant municipios where real wages declined but employment increased faster than the national population growth rate. More than one-third lived in apparently dynamic municipios, experiencing both real wage growth and faster-than-average employment growth. These areas absorbed more than half of net employment growth over the period. To elucidate this spatial variation, the authors estimate spatial labor supply and demand equations describing wage and employment changes of Brazilian municipios. They use Conley's spatial GMM technique to allow for instrumental variable estimation in the presence of spatially autocorrelated errors. The main findings include: (1) a very strong influence of initial workforce educational levels on subsequent wage growth (controlling for possibly confounding variables such as remoteness and climate); (2) evidence of positive spillover effects of own-municipio growth onto neighbors' wage and employment levels; (3) an exodus from farming areas; (4) relatively elastic response of wages to an increase in labor supply; and (5) evidence of a local multiplier effect from government transfers. "--World Bank web site